2014
DOI: 10.1136/annrheumdis-2014-eular.5281
|View full text |Cite
|
Sign up to set email alerts
|

THU0340 Efficacy of Transcutaneous Electrical Stimulation (TENS) and Kinesiotaping in Patients with Lateral Epicondylitis

Abstract: Background Lateral epicondylitis (LE) is one of the most common conditions affecting elbow [1]. Primary aims of treatment are pain relief and restoration of muscle condition [2]. There is a wide spectrum of treatments used in daily practice for management of LE such as analgesic medications, physical therapy, exercise and orthoses. Despite the large number of trials undertaken on LE, no treatment has been proven to be universally effective or generating consensus on its management [3]. Objectives The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A study done by Sari et al, aimed at comparing the efficacy of TENS (Transcutaneous Electrical Nerve Stimulation) and KT in the treatment of LE where they concluded that both the interventions combined had better effects on pain and functionality of the wrist after a 12 week intervention. But, these effects could not sustain till week 12 which could be because of the selflimiting nature of the condition and recommended for further studies [25].…”
Section: Kinesio-taping In Improving the Functionality/ Disability Of...mentioning
confidence: 99%
“…A study done by Sari et al, aimed at comparing the efficacy of TENS (Transcutaneous Electrical Nerve Stimulation) and KT in the treatment of LE where they concluded that both the interventions combined had better effects on pain and functionality of the wrist after a 12 week intervention. But, these effects could not sustain till week 12 which could be because of the selflimiting nature of the condition and recommended for further studies [25].…”
Section: Kinesio-taping In Improving the Functionality/ Disability Of...mentioning
confidence: 99%